The effect of commodity price changes and USD/IDR exchange rate on Indonesian mining companies’ stock return - Adi Rahadi Putra; Robiyanto Robiyanto (University of Merdeka Malang, 2019)
There are many variables that will be influencing stock return. Some of those variables are come from the commodity market, such as gold, price and crude oil price changes, and also come from the exchange rate market. This study is about to test the effect of changes prices of gold, silver, crude oil, and exchange rate to the stock return of mining sector companies in Indonesia. There are 48 companies engaged in the mining sector listed on the Indonesia Stock Exchange (IDX). From 48 companies this study uses the purposive sampling method to choose a sample within the criteria, and there are 13 selected companies that will be the object of this study. This study also used an analysis tool GARCH (1,1) to avoid abnormal data. Before advancing to GARCH (1,1) analysis, the data must be tested the stationary first by using the Augmented Dickey-Fuller Test (ADF) to make sure the data stationary or not by using level, 1st difference, and two difference. The result shows that gold has a significant positive effect on stock return mining sector companies such as INCO, KKGI, PTBA, and TINS. Silver has a significant positive effect on HRUM companies and negatively on RUIS. Crude oil has a significant positive effect on HRUM and PTBA firms. Exchange rates have a significant negative impact on companies. ANTM, CTTH, DOID, ELSA, HRUM, ITMG, and KKGI.JEL Classification: E03, F31, G11, G23DOI: https://doi.org/10.26905/jkdp.v23i1.2084